Effect of Educational Videos on Osteoporosis Knowledge Among Menopausal Women in Semidang Alas Village, Pagar Alam City - Reza Rahmawati; Delvia Novalisya; Delia Komalasari; Rizki Oktarini; Muthia Nurhidayah; Dian Handayani (JURNAL FARMASI DAN MAKANAN, 2026)
Osteoporosis is a bone-loss disease caused by decreased estrogen levels, predominantly affecting menopausal women. Limited access to health information in rural areas remains a major barrier to early prevention efforts. This study aimed to determine the effect of educational videos on osteoporosis knowledge levels among menopausal women in Semidang Alas Village, Pagar Alam City. A pre-experimental design with a one group pre-test–post-test approach was employed, involving 83 respondents selected through total sampling. Prior to the intervention, 61 respondents (73.50%) demonstrated poor knowledge. Following the educational video intervention, a significant improvement was observed, with 76 respondents (91.60%) achieving good knowledge levels. The paired t-test results indicated a p-value of 0.000, confirming a statistically significant effect of the educational video on osteoporosis knowledge. It is concluded that audiovisual media is an effective health education strategy, particularly for rural communities with limited access to health information.